Beyond nature and culture? - Scarso, Davide (Creativity Studies, 2013)
In this paper, we will analyze how anthropological thinking, in the last twenty years, has put the conceptual categories of Culture and Nature into radical questioning. Nature was “denaturalized” and deemed as a social construction that was specific to the history of Western world. But to avoid the alternative between nature and culture one should develop a “non-dualist” approach and, in this sense, we will then consider Tim Ingold's works. According to the British anthropologist, the nature and culture divide is usually the outcome of an assumption recurrent in anthropology, that according to which our cultural frames determine our perception of outside world. For Ingold, phenomenological thinking reversed the ontological priorities of Western rationalism.Anapus gamtos ir kultūros?Santrauka. Straipsnyje analizuojama, kaip per pastaruosius dvidešimt metų antropologinis mąstymas iš esmės sukvestionavo konceptualias kultūros ir gamtos kategorijas. Gamta buvo „denaturalizuota“ ir laikyta socialine konstrukcija, būdinga Vakarų pasaulio istorijai. Siekiant išvengti alternatyvos tarp gamtos ir kultūros, turėtų būti išplėtotas „nedualistinis“ požiūris. Todėl apžvelgiami Timo Ingoldo darbai. Remiantis britų antropologu, gamtos ir kultūros takoskyra paprastai yra antropologijoje pasikartojančios prielaidos rezultatas, pagal kurį kultūriniai rėmai apibrėžia mūsų išorinio pasaulio suvokimą. Ingoldo manymu, fenomenologinis mąstymas apvertė Vakarų racionalizmo ontologinius prioritetus.Reikšminiai žodžiai: konstrukcionizmas, kultūra, Ingoldas, gamta, fenomenologija.First published online: 03 Jan 2014